Itinerários da memória - práticas fotográficas, trajetórias profissionais e os sentidos da história - Ana Maria Mauad (Nuevo mundo - Mundos Nuevos, 2012)
The article analyses the contemporary photographic practices and its relationship to historical experience, throughout three photographs produced by three photographers, in three different moments of Brazilian history: 1959, 1961, 1984. The text is divided into three parts among which is discussed the itineraries of memory as a result of oral history methodological approach; photograph as a historical agent and, finally, the trajectory of the photographers and their discourses of recollection associated to an elaboration of a historical memory of present time.